The Impact of Adama City Expansion On Wonji Farm Land: From Food Security and Land Opportunity Perspective - Ermiyas, Abebayehu (ASTU, 2024)
Urban expansion's impact on agricultural land, poses a critical challenge globally, affecting food security and rural livelihoods. This study focuses on the repercussions of Adama City's expansion on Wonji farmland, evaluating its effects on food security and land opportunities. The study used geospatial data, government records, field surveys, and statistical methods to comprehensively assess the situation. Remote sensing and GIS were used to track land use and land cover changes, while field surveys and interviews were used to gather perspectives from farmers and stakeholders. The research utilizes the combination of both qualitative and quantitative analysis methods, including land use/land cover (LULC) analysis and farmer surveys, to provide a comprehensive understanding of the spatial and socioeconomic changes. The study reveals that both formal and informal settlements have significantly impacted Wonji farmland. Formal settlements, driven by government projects for infrastructure and residential areas, have led to structured urban expansion. In contrast, informal squatter settlements have caused unplanned sprawl, further straining agricultural land. From 1996 to 2023, farmland in Wonji decreased from 60.1% to 27.1%, while built- up areas increased from 6.9% to 48.1%. This shift has severely affected local livelihoods with 52.3% of respondents reported losing agricultural land, and 26.0% were completely displaced. Urban expansion has also impacted food security, about 45.5% drop in local food production, 31.9% decrease in affordable food options, and 15.3% loss of traditional food sources. These findings highlight the need for comprehensive strategies to balance urban development with food security. Policymakers, urban planners, and agricultural stakeholders must work together to address the challenges posed by urban expansion through better regulation, planning, and infrastructure development. This approach aims to ensure sustainable urban growth while preserving farmland and safeguarding food security for the local community.
Keywords: City expansion, Farmland, Food security, Land opportunity, Adama